Perceiving the world - Nanay, Bence (New York ; Oxford : Oxford University Press, 2010)
'Perceiving the World' offers 11 essays written especially for this book by some of the leading contemporary philosophers of perception: Susanna Siegel, Jesse Prinz, Adam Pautz, Mohan Matthen, Mike Martin, Sean Kelly, Benj Hellie, Andy Egan, Fred Dretske, Jerome Dokic & Jonathan Cohen.
Includes bibliographical references and index.
Description based on print version record.
Keywords: Perception (Philosophy); Philosophy